Integrated mission performance analysis of novel propulsion systems: analysis of a fuel cell regional aircraft retrofit - Pontika, Evangelia; Zaghari, Bahareh; Zhou, Tianzhi; Enalou, Hossein B.; Laskaridis, Panagiotis (American Institute of Aeronautics and Astronautics (AIAA), 2023)
This paper presents the development and application of an integrated, higher-fidelity framework developed within CHARM (the Cranfield Hybrid electric Aircraft Model) for the design, performance analysis and overall evaluation of novel electrified propulsion systems. The developed framework is used to model and analyze the performance characteristics of a Fuel Cell (FC) regional aircraft system in comparison with a conventional regional aircraft and a hydrogen gas turbine regional aircraft retrofit. The FC propulsion system and the hydrogen gas turbine are retrofitted to the same conventional aircraft platform. Physics-based aircraft performance calculations, propeller maps, gas turbine component maps, off-design cycle analysis, electric component maps, calculations for the electric power management and distribution, and a Proton-Exchange Membrane FC (PEMFC) configuration sized to cover the power requirements of a regional aircraft, are integrated within this framework to capture the performance and interaction of components, sub-systems and aircraft during any flight mission and conditions. The aircraft performance, the propulsion system performance characteristics and the emissions of the three technologies are calculated and discussed to understand the challenges and opportunities of using hydrogen-electric propulsion (FC). The effect of capturing the variable mission parameters and flight phases on the performance of the electric power system and FC is presented and compared against a lower fidelity modeling approach for the electric powertrain. The sensitivity of the FC propulsion system and its attributes to varying mission requirements (island-hopping, range, cruise altitude, ambient conditions), as well as the change in the consumed fuel, are demonstrated. This framework can be used to inform the decision-making for the design of electric components and thermal management systems (TMS), and the importance of capturing the trade-off between mass, efficiency and operational constraints in the design process is highlighted. Also, the off-design performance of the electric power system designs and FC is modeled to decide if the design is within acceptable limits under various conditions, and capture the effect of mission requirements and flight conditions on the energy consumption of the overall aircraft system. Finally, a parametric analysis addresses the effect of power density improvement with future technology on the energy per passenger and feasibility of the FC regional aircraft.